Santri dan Politik: Revitalisasi Peran Santri dalam Mewujudkan Indonesia Emas 2045 - Dalailul Choir; Wahyu Trisno Aji (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
This paper aims to explain the importance of political literacy for Islamic boarding school students (santri) as a means to achieve Indonesia's golden age by 2045. This research focuses on qualitative methods with a literature study approach, focusing on primary data in the form of documentation, including books, journals, articles, and other literature related to political discussions and Islamic boarding school students. The results show that "santri" (literate people) or those seeking religious knowledge in Islamic boarding schools (pesantren) must possess broad insight and be tolerant of political apathy. Santri political awareness is essential for them to contribute to improving and strengthening Indonesia's political system with noble religious values. Santri involvement in politics also serves as a means to raise awareness as active citizens, strengthen nationalism, and make politics a form of service, not personal ambition. Politically literate students will be able to face various social and political challenges wisely and contribute to maintaining the nation's stability and progress. Therefore, a joint effort is needed to strengthen political education, both for santri and the general public, so that by 2045, Indonesia will have an intelligent, ethical generation ready to lead the nation towards a bright future.